Kemampuan Berpidato pada Pembelajaran Bahasa Jawa Siswa Sekolah Menengah Pertama - Utami, Sri (Jurnal Likhitaprajna, 2024)
Making a speech is one of the activities in implementing one aspect of language skills, namely the speaking aspect. Speaking ability is an interaction activity using language, which is carried out by individuals and groups. The ability to speak also helps in any activity of communicating directly to convey ideas or opinions. Likewise, in learning Javanese there is material that teaches students to master Javanese or the ability to communicate between students in communicating using Javanese. Meanwhile, giving a speech itself is the activity of speaking in public to convey information which also contains a message. One way to make students skilled at giving speeches is that this research examines the ability to make speeches in Javanese language learning. This research aims to provide descriptive information about giving speeches using Javanese in terms of fluency, attitude, and facial expressions so that it can be realized that the activity of learning to make speeches using Javanese is a holistic learning that can be used as a character education for students in retaining language culture Java. The method in this research uses qualitative research with a descriptive approach. Qualitative research is research that has the aim of understanding phenomena regarding various perceptions, motivations and actions holistically, or by means of descriptions in the form of words or language in a natural context by utilizing various scientific methods. Therefore, this method is used in this research, in this case to describe and describe speech abilities in Javanese language learning. From the results of the analysis, it was concluded that students learning to give speeches were able to give speeches in Javanese. This is evident from several aspects of the assessment, namely; aspects of fluency, attitude and facial expressions. From these aspects, students assessing the fluency aspect got the highest score, namely very good.